The Prose and Drama of an Outstanding Poet, Voĺha Hapiejeva - McMillin, Arnold (Przegląd Wschodnioeuropejski, 2019)
This article reviews the prose and drama of Voĺha Hapiejeva up to 2018. The main themes of her work are: feminism, gender and sexual relations in a patriarchal society, and also various aspects of contemporary life, A Candidate of Science, she brings into her works, humorously, a variety of linguistic and grammatical forms. Her work is notable for its strong use of imagery, lively dialogues and many, especially in the plays, much absurdity. Without doubt Hapiejeva is not only one of boldest and most original of the promising Belarusian poets of our day, but also a very talented prose writer and dramatist.